Analisis Kinerja Keuangan Terhadap Harga Saham Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Nadia Irfan, Rezky; Hamzah, Hajrah; Nuraisyiah (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to determine the effect of Current Ratio, Earnings Per Share (EPS), and Debt to Equity Ratio (DER) on the stock prices of mining companies listed on the Indonesia Stock Exchange. Data were collected from coal mining companies listed on the Indonesia Stock Exchange over a five-year period. Data were analyzed using multiple linear regression analysis. The results show that CR, EPS, and DER have a significant influence on the stock prices of mining companies, both partially and simultaneously